Watch your language! : mother tongue and her wayward children - Gorrell, Robert M. (University of Nevada Press, 1994)
Most language mavens seem to come not to praise English, but to bury it; they constantly warn us of the imminent demise of our mother tongue. Not to worry, says Robert Gorrell. In this lively, playful celebration of the joys and power of language, he points to all the signs that show English to be alive and well, and, like any other living thing, constantly evolving.